Revealing Coprophilous Basidiomycetes in Sri Lanka: An Integrative Taxonomic Assessment of Dung‐Inhabiting Mushrooms - Nethmi M. Perera; Thivanka M. Peiris; Helani H. Munasinghe; Mayuri Munasinghe; Isuru Sakbo Uyangoda; Milan C. Samarakoon; Danushka S. Tennakoon; Buddhika P. Dharmasena; Samantha C. Karunarathna; Kasun M. Thambugala (New Zealand Journal of Botany, 2026)
Coprophilous fungi inhabit animal dung and play a crucial role in ecological balance by decomposing animal waste and serving as a food source for coprophagous and mycophagous arthropods. This study aimed to systematically characterize the diversity of coprophilous basidiomycetes across selected regions of Sri Lanka, and it characterized seven coprophilous basidiomycete specimens representing five distinct species from selected sites in Sri Lanka using both morphological and molecular methods. Specimens associated with elephant dung and horse manure were obtained from the Colombo, Gampaha, Nuwara Eliya, and Ratnapura districts. Taxonomical identification was achieved via integrated macro‐ and micromorphological analyses. Morphological characterization relied on detailed macro and micromorphological observations, while phylogenetic relationships were inferred from combined ITS and nLSU sequence data analyzed using maximum likelihood and Bayesian methods. Five species were identified and described at the species level, representing the first documented records of these taxa in Sri Lanka. These species include Conocybe volvata , Coprinopsis cinerea , Narcissea cordispora , Panaeolus antillarum , and Panaeolus cyanescens . The findings enhance the documentation of coprophilous fungal diversity in Sri Lanka and establish a foundation for future ecological and biotechnological research on dung‐inhabiting fungi in tropical ecosystems.